Trevo 6 × 25mm vs. 4 × 30mm in Mechanical Thrombectomy of M1 LVO - Oliver, Marion John; Brereton, Emily; Khan, Muhib A.; Davis, Alan; Singer, Justin (Frontiers in Neurology, 2021)
Objectives: Our primary objective was to determine the successful rate of recanalization of M1 large vessel occlusion using either the Trevo 4 × 30 mm or 6 × 25 mm stent during mechanical thrombectomy. Our secondary objectives were to determine differences between the use of these two stent retrievers regarding first-pass effect, periprocedural complications, and mortality in the first 90 days. Methods: This is a retrospective cohort study. Data regarding the stent used, recanalization, number of passes, periprocedural complications, and mortality were determined via our mechanical thrombectomy database along with chart review. Conclusion: When comparing Trevo 4 × 30 mm to 6 × 25 mm stent retrievers used in mechanical thrombectomy for middle cerebral artery large-vessel occlusion causing stroke, there is no statistically significant difference in successful recanalization rates, first-pass effect, perioperative complications, or mortality at 90 days. Studies like this will hopefully lead to further prospective, randomized controlled trials that will help show experts in the field an additional way to perform this procedure effectively and safely.